Tingkat Daya Tahan Kardiovaskuler Tim Basket Putri Aldabra Academy Surabaya - Hari, Al-Fitri Zahra Fadhilah; Anna Noordia; Himawan Wismanadi; Ratna Candra Dewi (Jurnal Bina Ilmu Cendekia, 2025)
This study aims to determine the cardiovascular endurance level of the girls' basketball team at Aldabra Academy Surabaya. Cardiovascular endurance is a vital component of physical fitness that greatly influences athlete performance, particularly in basketball, which requires repeated and high-intensity physical activity. This study employed a descriptive quantitative method with a survey approach and utilized the Beep Test to estimate VO₂max values. The subjects consisted of 12 female basketball players from Aldabra Academy. The results showed that most players were in the good category (58.3%), followed by the very good category (33.3%), and only one player (8.3%) was in the fair category. The average VO₂max was 46.6 ml/kg/min with a standard deviation of 5.01 ml/kg/min, indicating a generally good and evenly distributed level of cardiovascular fitness within the team. These findings can serve as a reference for coaches in designing more focused training programs aimed at maintaining and improving aerobic capacity across the team.